Coyuntura Económica - María Carolina Rozo; Emma Beatriz Castro U; Ángela Patricia Bedoya; Carlos Ignacio Chávez; Guillermo Aponte (Revista de Economía & Administración E-ISSN 2463-1035 ISSN 1794-7561, 2012)
Coyuntura económica